STAT3 Signaling Is Activated Preferentially in Tumor‐Initiating Cells in Claudin‐Low Models of Human Breast Cancer. (October 2014) - Wei, Wei; Tweardy, David J.; Zhang, Mei; Zhang, Xiaomei; Landua, John; Petrovic, Ivana; Bu, Wen; Roarty, Kevin; Hilsenbeck, Susan G.; Rosen, Jeffrey M.; Lewis, Michael T.
Abstract In breast cancer, a subset of tumor‐initiating cells (TIC) or "cancer stem cells" are thought to be responsible for tumor maintenance, treatment resistance, and disease recurrence. While current breast cancer stem cell markers (e.g., CD44high/CD24low/neg, ALDH positive) have allowed enrichment for such cells, they are not universally expressed and may actually identify distinct TIC subpopulations in the same tumor. Thus, additional markers of functional stem cells are needed. The STAT3 pathway is a critical regulator of the function of normal stem cells, and evidence is accumulating for its important role in breast cancer stem cells. However, due to the lack of a method for separating live cells based on their level of STAT3 activity, it remains unknown whether STAT3 functions in the cancer stem cells themselves, or in surrounding niche cells, or in both. To approach this question, we constructed a series of lentiviral fluorescent (enhanced green fluorescent protein, EGFP) reporters that enabled flow cytometric enrichment of cells differing in STAT3‐mediated transcriptional activity, as well as in vivo/in situ localization of STAT3 responsive cells. Using in vivo claudin‐low cell line xenograft models of human breast cancer, we found that STAT3 signaling reporter activity (EGFP+) is associated with a subpopulation of cancer cells enriched for mammosphere‐forming efficiency, as well as TIC function in limiting dilution transplantation assays compared to negative or unsorted populations. Our results support STAT3 signaling activity as another functional marker for human breast cancer stem cells thus making it an attractive therapeutic target for stem‐cell‐directed therapy in some breast cancer subtypes. Stem Cells2014;32:2571–2582